Evaluation of waste composition for biochar production as a sustainable waste management approach - Putri, Aurellia Nur Islami (Waste Handling and Environmental Monitoring, 2024)
Background: To meet human life needs, fuel energy is obtained from fossil sources, such as coal, found in the Earth's crust. However, non-renewable energy sources in the Earth's crust will eventually run out. One alternative fuel is the production of biobriquettes from various types of waste. Methods: Using a literature review method, this study aims to determine which waste is most suitable for use in the production of biobriquettes. The samples taken are journals sourced from Google Scholar ranging from 2017 to 2022 that align with the discussion topic. Findings: Among various raw materials, the best waste for biobriquette production is found to be a mixture of dacron waste and corn cob, with a moisture content of 3.45% and a carbon value of 7986.45 cal/g. Conclusion: The results of the above study indicate that the production of biobriquettes from dakron waste and corn cobs is the best option because it yields the highest calorific value and the lowest moisture content, in accordance with SNI 01/6235/2000. Novelty/Originality of this article: This study presents a novel approach by identifying a specific combination of dacron waste and corn cob for biobriquette production, showcasing its superior calorific value and low moisture content, thus contributing to sustainable energy solutions and waste management practices.